PA01.11. A retrospective case study of ayurvedic treatment of ashmaräª (renal calculi) - Jangid, Chhagan (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: Now a day's occurrence & recurrence of Ashmara (Renal Calculus) are very common & its rate of incidence is alarmingly increasing. Some acute cases require immediate attention to relieve from severe pain. Even surgery is recommended if a calculus is larger in size because it can cause many complications. Conservative line of treatment is recommended if calculi are small in size, non obstructive, post operative and in the cases of recurrence. For the conservative treatment of Renal Calculi, Ayurvedic medicines are being used successfully since centuries for removing the calculi in addition to protecting its formation. METHOD: This study was conducted in the Department of Ayurveda, Indira Gandhi E.S.I. Hospital, and Delhi. The patients were selected irrespective of their age, sex, occupation etc. in the Ayurvedic OPD and treated with classical as well as some patent & proprietary Ayurvedic medicines for the minimum period of two months according to type of calculus along with associated signs & symptoms. RESULT: Since December 2009 to September 2011, total 500 patients were registered. Out of them only 400 cases were selected for this retrospective study that completed minimum course of two months. In most of the cases severity & episodes of pain markedly reduced, number and size of calculi, hydronephrosis (mild to mod), burning micturition, nausea & vomiting etc. also shown decreasing pattern and 90 cases were completely cured. CONCLUSION: Ayurvedic medicines are highly effective in the treatment of Ashmara, which shows their Lithotripsic action.